Philadelphia, June 1876 Paper - A History of the Bessemer Manufacture in America - Robert W. Hunt (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The memorable features of American history have been making fast during the last century, and notably so since 1860; and they are by no means confined to political or to any one branch of scientific development. Of all the industrial arts, none show a greater change or 'a mightier progress than the Bessemer manufacture. And this year, while we are celebrating the first centennial of our national life, we can also celebrate the first decennial of American Bessemer practice. While not forgetting or undervaluing what has been done in other countries, I have thought that a brief history of the introduction and development of the Pneumatic or Bessemer process in America would be of interest. In 1863 the Kelly Pneumatic Process Company was formed and an arrangement entered into with William Kelly, who had taken out letters-patent of the United States, Nos. 16,444; 17,628, reissued as 505; 18,910, dated January loth, 1857; June 23d, 1857; November 36, 1857; and December 22d, 1867, respectively. This association mas composed of the Cambria Iron Company, E. B. Ward, Park Brothers & Co., Lyon, Shorb & Co., Z. S. Durfee, and, later, Chouteau, Harrison & Valle joined the combination. Not satisfied with possessing the control of the Kelly patent, they sent Mr. 2. S. Durfee to England, to secure for this country Mushet's patent on recarburization, No. 17,389, dated May 26th, 1857, the same having been taken out in England on September 22d, 1856. In this Mr. Durfee was successful. Previous to the application of William Kelly for a patent, Henry Bessemer, of England, had taken out patents dated February 12th, 1856, and August 25th, 1856, in this country. Kelly claimed priority in the discovery of the principles of the process, and the Patent-office allowed his claim by granting him his patents. In the autumn of 1862 Mr. Alexander L. Holley, while in England, was impressed with the importance of Mr. Bessemer's invention, and so fully foresaw its future, that, upon his return to the United States, he induced Messrs. John A. Griswold and John F. Winslow, of Troy, New York, to join him in endeavoring to possess Bessemer's American patents. Mr. Holley returned to England in